Effects of fiber length and content on the performance of ultra-thin wearing course modified by basalt fibers. (27th December 2021) - Lou, Keke; Xiao, Peng; Wu, Bangwei; Kang, Aihong; Wu, Xing; Shen, Qianchao
Highlights: Ultra-thin wearing course modified by basalt fiber with high performance was developed. The performance of ultra-thin wearing course and the dispersion of fibers were evaluated. Optimum fiber content and length are related to mixture gradation. Excessive content and overlong length are negative to fiber dispersion. Abstract: Ultra-thin wearing course (UTWC) is a kind of functional layer widely used in road maintenance and construction, which is beneficial to prolong its service life. However, the performance of UTWC is frequently insufficient, especially cracking and raveling resistance. To investigate the effects of basalt fiber (BF) length and content on the performance of UTWC, basalt fibers with varied lengths (3 mm, 6 mm) and contents (0.2%, 0.3%, 0.4% and 0.5%) were selected. The macro-performance of UTWC were evaluated by wheel tracking test, uniaxial penetration test (UPT), low temperature bending beam test, semi-circle bending test (SCB), immersion stability test, Cantabro test and skid resistance test, besides scanning electron microscope (SEM) and fiber extraction test were employed to analyze the reinforcement mechanism and dispersion properties of basalt fibers. The results showed that compared with the neat one, the comprehensive performance of UTWC modified by basalt fibers was improved greatly, especially cracking and raveling resistance, which is influenced by fiber length and content. Fibers could form a three-dimensional network in the mixture, which is able to improve the integrity of the mixture and suppress the development of cracks effectively. However, the large contents and long lengths had negative effects on the fiber dispersion. Furthermore, based on the grey target theory, 3 mm basalt fiber is more suitable for AC-10, while 6 mm basalt fiber is more suitable for SMA-10. The optimum content of basalt fiber for AC-10 and SMA-10 is 0.2% and 0.3%, respectively. These findings provide a significant guidance for the application and promotion of UTWC.